2003
DOI: 10.1103/physreve.67.015501
|View full text |Cite
|
Sign up to set email alerts
|

Search for the prewave zone effect in transition radiation

Abstract: Results of the first experimental search for the effect of the prewave zone in near-infrared transition radiation are presented. A substantial difference in the spatial distribution of transition relation for two different wavelengths (450 nm and 1600 nm) was observed. Experimental data are in a good, though not complete, agreement with the theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 5 publications
6
18
0
Order By: Relevance
“…It corresponds to distances for which the angular distribution of the electromagnetic field is affected by the transverse dimension of the source. Transition radiation in the prewave zone was then studied experimentally [5] showing good agreement with theoretical expectations. Far field conditions can only be considered valid for distances from the source much larger than γ 2 λ/2π, which implies that beam diagnostics based on TR radiation using long wavelength or for very high beam energies will be perturbed by prewave zone effects [6,7].…”
mentioning
confidence: 74%
“…It corresponds to distances for which the angular distribution of the electromagnetic field is affected by the transverse dimension of the source. Transition radiation in the prewave zone was then studied experimentally [5] showing good agreement with theoretical expectations. Far field conditions can only be considered valid for distances from the source much larger than γ 2 λ/2π, which implies that beam diagnostics based on TR radiation using long wavelength or for very high beam energies will be perturbed by prewave zone effects [6,7].…”
mentioning
confidence: 74%
“…In both cases the radiation was considered under several conditions, such as infinite perfectly conducting target and wave zone approximation, which impose some restriction on the field of application. Later further studies were conducted in order to generalize the obtained results beyond the ideal conditions, therefore finite screen size and observation in pre-wave zone [4,[9][10][11]. Here and further we use terms wave and pre-wave zones as they were used by Verzilov in [9].…”
Section: Theory and Simulationsmentioning
confidence: 98%
“…The TR and DR can be considered as an interaction between electron field and the target material. At high energy, due to the relativistic effects, the electron field becomes a flat disc in a plane perpendicular to the electron velocity vector, whose ''effective'' size can be estimated as $ kc [4,11,12]. For the wave zone approximation [3,6] the size of the target was considered as infinite with respect to the electron field, and in order to satisfy this condition the size of the target should be larger than the effective size of the electron field.…”
Section: Theory and Simulationsmentioning
confidence: 99%
“…For the case of TR such situation was first theoretically considered in [18,19]. The experimental investigations of TR characteristics in the prewave zone are reported in [20][21][22]. In these papers it was shown that radiation spectral-angular distribution registered by a pointlike detector in this situation significantly differs from the one registered in the wave zone (outside the formation region).…”
Section: Introductionmentioning
confidence: 99%